MENGUAK EFEK PENURUNAN TARIF PAJAK PENGHASILAN DI MASA PANDEMI COVID-19 - Alfi Bryan Garin Susanto (Universitas Sains dan Teknologi Komputer, 2021)
This article explains the effect of lowering income tax rates during the COVID-19 pandemic. The government's role in maintaining economic stability is carried out by issuing fiscal policies, in terms of taxation, namely by reducing the Corporate Income Tax rate. This research intends to find out the results of a decrease in corporate income tax rates affecting a decrease in current taxes deposited into the state treasury, a decrease in the total income tax burden, and recording in the income statement financial statements. The informants of this research are members of the Tax Rules Update Forum. This type of qualitative research uses a netnography approach. The reduction in current taxes deposited into the state treasury benefits the company by minimizing the costs incurred for the obligation to deposit state taxes. Companies that have deferred tax liabilities receive deferred tax benefits recorded in the balance sheet account, so the total income tax expense has decreased. In recording the income statement, the company has deferred tax assets adding to the deferred tax expense. Deferred tax expense in profit or loss account.